Preparation Methods and Multifunctional Applications of Functionalized Electrospun Nanofibers for Biomedicine - Jingwen Liu; Kai Wang; Fengying Jin; Jiayi Li; Yile Bin; Xiaofei Qian (Nanomaterials)
Electrospinning has emerged as a versatile and cost-effective technique for fabricating nanofibers with a high surface area, tunable morphology, and exceptional mechanical properties, demonstrating significant potential for applications in biomedicine. This review summarizes the main parameters of the electrospinning process and fabrication methods of functionalized electrospun nanofibers (FENFs) through one-step functionalization and post-functionalization. The applications of FENFs, with their antibacterial activity, anti-inflammatory effects, and tissue regenerative effects, as well as their potential in drug delivery systems and sensors, showcase their capability to address challenges in wound healing, cancer therapy, and health monitoring. Current limitations and future research directions are also identified. This review provides valuable insights for advancing research on nanofiber-based materials and their practical implementations.